Animism and Science - Eyghen, Hans van ca. 21. Jh. (Religions, 2023)
I discuss whether animism, the worldview that (some) objects, plants and animals are capable of communication, rational reflection and intentional action, is in conflict with contemporary science. I distinguish two conflicts. The first points to conflicting claims regarding the abilities of objects, plants and animals made by scientists and animists (agential vs. non-agential). I argue that the alleged conflict can be diffused by noting that science and animism advance different ways of looking at the world. The second conflict notes discrepancies between how animists treat nature and all therein (with respect and reverence) and how science does (instrumentalized). I argue that this conflict is more difficult, if not impossible, to overcome.